Employing popular folk music and songs in the children's theater (Journal of the College of Basic Education, 2022)
This study is concerned with defining the importance of traditional folk music and songs, and employing them within theatrical performances for children, which are of great benefit in expanding the cognitive, mental and psychological horizons of the child, and add joy, pleasure and response to musical games based on the link between rhythm, play and acting, as the researcher divided the research into four Chapters, including the first, the methodological framework of the research, represented by the problem, importance and objective of the research,